COMPREHENSIVE REHABILITATION OF DISABLED CHILDREN WITH BILATERAL THROUGH-CLEFT LIP AND PALATE IN KRASNODAR REGION - F. S. Ayupova; M. N. Mitropanova; V. V. Volobuev; A. F. Verapatvelian; S. S. Guschina; O. A. Pavlovskaya; A. R. Voskanyan (Кубанский научный медицинский вестник, 2018)
Aim. This study was designed to evaluate the immediate and long-term results of the Protocol of complex rehabilitation of 15 Kubanskij nauchnyj medicinskij vestnik 2018; 25 (5) children with bilateral through-cleft lip and palate (BTCLP) developed by the Department of pediatric dentistry, orthodontics and maxillofacial surgery of KSMU.Materials and methods. There was conducted the evaluation of the immediate and long-term results of the complex treatment of 25 patients with BTCLP aged 0 to 18 years according to the Protocol developed by the Department of pediatric dentistry, orthodontics and maxillofacial surgery of KSMU.Results. There was carried out a detailed analysis of the results of the application of the function-forming plate (FFP) in patients with BTCLP aged 0 to 1 year. The results of the models measurement in dynamics showed a significant growth and development of the upper jaw, the approximation of the shape and size of the upper alveolar arc to the norm, reducing the distance between its fragments to the minimum. There was established that long-term gradual orthodontic treatment provides conditions for physiological growth and development of the facial skeleton and for the formation of physiological occlusion in children with BTCLP. The usage of gentle methods of uranoplasty reduces the risk of dentoalveolar anomalies in children with BTCLP. The complex of therapeutic measures and terms of surgical intervention should be planned individually. The elimination of the defects of the alveolar process of the upper jaw by the method of autoosteoplasty is a necessary step in the complex rehabilitation of children with BTCLP during the periods of changing and forming permanent dentition. The planning of the stage of prosthetics of patients with BTCLP is individual and involves the creation of conditions for fullfledged functions of chewing, swallowing and speech, and it is recommended to carry it out with the help of modern aesthetic constructions that ensure the preservation of the results of the complex, including orthodontic, treatment.Conclusion. The analysis of the photographs of the face, TRG, CT and jaws diagnostic models obtained during the treatment of children and adolescents with congenital cleft lip and palate confirms the high morphofunctional and aesthetic result of the application of the developed at the Department of pediatric dentistry, orthodontics and maxillofacial surgery of KSMU Protocol of comprehensive rehabilitation of children with BTCLP.